TATA CARA PENAGIHAN PAJAK DENGAN SURAT TEGURAN, SURAT PAKSA, SITA DAN LELANG DI KPP PRATAMA JAKARTA SAWAH BESAR SATU - Eka Pujianthi (Universitas Muhammadiyah Kendari, 2018)
The purpose of this research is to determine the procedure of tax collection with letter of reprimand and letter of compulsion at KPP Pratama Jakarta Sawah Besar Satu. This type of method used in this research is qualitative descriptive. The data used in this research is the disbursement of tax arrears, tax arrears disbursement targets, the receipt with letter of reprimand, letter of compulsion seizure and auction for the period 2012-2015. The data were obtained from interview and documentation. The results of this research indicate that procedure of tax collection with letter of reprimand, and letter of compulsion at KPP Pratama Jakarta Sawah Besar Satu in accordance with Act No. 19 of 2000 about tax collection with letter of compulsion.